A Meta-Analysis to Understand the Variability in Reported Source Levels of Noise Radiated by Ships From Opportunistic Studies - Chion, Clément; Lagrois, Dominic; Dupras, Jérôme (Frontiers in Marine Science, 2019)
Commercial shipping is identified as a major source of anthropogenic underwater noise in several ecologically sensitive areas. Any development project likely to increase marine traﬃc can thus be required to assess environmental impacts of underwater noise. Therefore, project holders are increasingly engaging in underwater noise modeling relying on ships’ underwater noise source levels published in the literature. However, a lack of apparent consensus emerges from the scientific literature as discrepancies up to 30 dB re 1µPa are reported for ships’ broadband source levels belonging to the same vessel class and operating under similar conditions. We present a statistical meta-analysis of individual ships’ broadband source levels available in the literature so far to identify which factors likely explain these discrepancies. We collated ships’ source levels from the published literature to construct our dataset. A Generalized Linear Mixed Model was applied to the dataset to statistically assess the contribution of intrinsic (related to ships’ static and dynamic attributes) and extrinsic factors (related to both the protocol for hydroacoustic data acquisition and the noise data reduction procedure) to the reported broadband source levels. Amongst intrinsic factors, ships’ speed-over-ground (15.13 × log 10 (v); p-value < 0.001), ships’ width (12.07 × log 10 (b); p-value < 0.001), and ships’ class (-6.07 − 2.09 dB re 1µPa; p-value ∈ [< 0.001 − 0.031]) have shown the strongest correlations with broadband source levels. The hydrophone-to-source closest point of approach (-4.81 dB re 1µPa nm −1 ; p-value < 0.001) and the computation of monopole source levels (22.33 dB re 1µPa; p-value = 0.003) instead of range-independent dipole measurements contribute the most to explain the reported ships’ broadband source levels variability amongst extrinsic factors. Our meta-analysis conﬁrms a consensus that speed regulation can effectively reduce instantaneous ships’ source levels. The abuse of a dipole approach for data analysis and spreading laws for transmission loss leads to a generalized under-estimation of the ships’ source levels retrieved from the literature. This could be addressed by a wider adoption of standardized methods of hydrophone-based sound recordings and of data processing to homogenize results and facilitate interpretation for environmental impact assessment.